ROBLEMATIKA PERLINDUNGAN PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI INDONESIA PERSPEKTIF HUKUM ISLAM - Bustanul Ariin; Lukman Santoso (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
The case of household violence physically or psychologically nowadays is often we hear. That reality factually shows that the violence in the household toward wife, is the common phenomenon in the societal environment. This case is sure not away from the social construct which is developed in the middle of society that s husband is the head of family and has a full authority to the part of family including wife. In that context this research is making effort to peel off how the problem of protecting implementation toward women in violence (KDRT) and Islam gives the answers. In the context of women protection in the household, Al-Quran texts give a lot of answers which order to make the relationship of household as ma’ruf in the meaning of equal, fair, and democratic. In the terminology of Ushul Fiqh, this concerning agrees with what the goals of law are, that is the law toward ive aspects (al-kulliyat al-khams), which one is soul protection (hifz an-nafs). This explains that Islamic law brings the mission of protection, it is as a God’s mercy to all humans in this world. It is also harmonization with the law of women protecting in Indonesia.